Galactoside-Based Molecule Enhanced Antimicrobial Activity through Acyl Moiety Incorporation: Synthesis and In Silico Exploration for Therapeutic Target - Faez Ahmmed; Samiah Hamad Al-Mijalli; Emad M. Abdallah; Ibrahim H. Eissa; Ferdausi Ali; Ajmal R. Bhat; Joazaizulfazli Jamalis; Taibi Ben Hadda; Sarkar M. A. Kawsar (MDPI AG, 2023)
In this study, a series of galactoside-based molecules, compounds of methyl β-d-galactopyranoside (MDGP, 1), were selectively acylated using 2-bromobenzoyl chloride to obtain 6-O-(2-bromobenzoyl) substitution products, which were then transformed into 2,3,4-tri-O-6-(2-bromobenzoyl) compounds (2-7) with various nontraditional acyl substituents. The chemical structures of the synthesized analogs were characterized by spectroscopic methods and physicochemical and elemental data analyses. The antimicrobial activities of the compounds against five human pathogenic bacteria and two phyto-fungi were evaluated in vitro and it was found that the acyl moiety-induced synthesized analogs exhibited varying levels of antibacterial activity against different bacteria, with compounds 3 and 6 exhibiting broad-spectrum activity and compounds 2 and 5 exhibiting activity against specific bacteria. Compounds 3 and 6 were tested for MIC (minimum inhibitory concentration) and MBC (minimum bactericidal concentration) based on their activity. The synthesized analogs were also found to have potential as a source of new antibacterial agents, particularly against gram-positive bacteria. The antifungal results suggested that the synthesized analogs could be a potential source of novel antifungal agents. Moreover, cytotoxicity testing revealed that the compounds are less toxic. A structure-activity relationship (SAR) investigation revealed that the lauroyl chain [CH3(CH2)10CO-] and the halo-aromatic chain [3(/4)-Cl.C6H4CO-] in combination with sugar, had the most potent activity against bacterial and fungal pathogens. Density functional theory (DFT)-calculated thermodynamic and physicochemical parameters, and molecular docking, showed that the synthesized molecule may block dengue virus 1 NS2B/NS3 protease (3L6P). A 150 ns molecular dynamic simulation indicated stable conformation and binding patterns in a stimulating environment. In silico ADMET calculations suggested that the designed (MDGP, 1) had good drug-likeness values. In summary, the newly synthesized MDGP analogs exhibit potential antiviral activity and could serve as a therapeutic target for dengue virus 1 NS2B/NS3 protease.